1983
DOI: 10.1007/bf00405191
|View full text |Cite
|
Sign up to set email alerts
|

Bi-phasic composition of trans-root electrical potential in roots of Plantago species: involvement of spatially separated electrogenic pumps

Abstract: The effect of oxygen on the trans-root potential (TRP) of excised roots in Plantago media L. and P. maritima L. was investigated. Two distinct reactions were found. In some experiments (type A roots) the reaction of TRP to anoxia was bi-phasic, and this reaction fits well into a model, assuming the presence of two spatially separated proton pump sites in the roots: one at the plasmalemma of epidermal and cortical cells and the other at the symplast/xylem interface. The two pumps work in opposite directions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 21 publications
3
47
1
Order By: Relevance
“…Assuming that a radial electrical gradient did not exist in the symplast (Dunlop & Bowling 1971a), the TRP was considered to be the difference between the membrane potentials of cortical cells and xylem parenchyma cells (both membranes being opposite in polarity with respect to the overall potential difference; Dunlop & Bowling 1971a,b). Similar conclusions were obtained when the effect of sugars on cortical membrane potentials and on the TRP were studied (Kennedy & Steward 1982) as well as when roots were treated with anoxia (De Boer, Prins & Zanstra 1983). These data have been interpreted by analogue electrical circuits of the root (Ginsburg 1972;Cortes 1993;Due 1993).…”
supporting
confidence: 71%
“…Assuming that a radial electrical gradient did not exist in the symplast (Dunlop & Bowling 1971a), the TRP was considered to be the difference between the membrane potentials of cortical cells and xylem parenchyma cells (both membranes being opposite in polarity with respect to the overall potential difference; Dunlop & Bowling 1971a,b). Similar conclusions were obtained when the effect of sugars on cortical membrane potentials and on the TRP were studied (Kennedy & Steward 1982) as well as when roots were treated with anoxia (De Boer, Prins & Zanstra 1983). These data have been interpreted by analogue electrical circuits of the root (Ginsburg 1972;Cortes 1993;Due 1993).…”
supporting
confidence: 71%
“…For example, K + -ion gradients in the root tissue as revealed with the electronprobe microanalysis technique Dunlop & Bowling 1971a) could not be detected by successive radial insertion of a K + -selective microelectrode into the root tissue. Furthermore, measurements of transroot potentials lead to conflicting data concerning the role of stelar proton pumps (Dunlop 1973;Dunlop & Bowling 1971b;De Boer et al 1983).In this communication we demonstrate that the problems of the microelectrode technique mentioned above can be overcome by incorporation of a potential-recording Ag/AgCl wire into the xylem pressure probe (Balling & Zimmermann 1990; Schneider et al 1997a,b). Such a xylem pressure-potential probe has the advantages (1) that a proper probing of a vessel is indicated by the pressure signal, (2) that clogging of the microcapillary tip can easily be removed by the displacement of the metal rod within the pressure probe and (3) that the integrated electrode in the probe can be used to determine separately the radial electrical resistance of the root (which is an indicator for a short-circuit of the tissue).…”
mentioning
confidence: 63%
“…For example, K + -ion gradients in the root tissue as revealed with the electronprobe microanalysis technique Dunlop & Bowling 1971a) could not be detected by successive radial insertion of a K + -selective microelectrode into the root tissue. Furthermore, measurements of transroot potentials lead to conflicting data concerning the role of stelar proton pumps (Dunlop 1973;Dunlop & Bowling 1971b;De Boer et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results may also be compared with data from perfusion experiments in which young roots of herbaceous species were used. Here the opposite effects of anoxia and FC on the pH of the perfusion liquid flowing through the vessels of primary xylem indicated that the vascular sap pH depends on the activity of the plasma membrane H + -ATPase of cells probably located in the stele or surrounding the stele (De Boer et al, 1983;Clarkson and Hanson, 1986). Immunocytolocalization of this enzyme or in situ expression in sections of young roots indicated that the H + -ATPase was highly concentrated in the endodermis (Parets-Soler et al, 1990) or pericycle (Samuels et al, 1992), which is adjacent to the primary vessels.…”
Section: Resultsmentioning
confidence: 99%